Fighting phishing everything you can do to fight social engineering and phishing - Grimes, Roger A.; Just, John N. (Ascent Audio, 2024)
Fighting Phishing: Everything You Can Do to Fight Social Engineering and Phishing serves as the ideal defense against phishing. Unlike most anti-phishing books, which focus only on one or two strategies, this book discusses all the policies, education, and technical strategies that are essential to a complete phishing defense. This book gives clear instructions for deploying a great defense-in-depth strategy to defeat hackers and malware. Written by the lead data-driven defense evangelist at the world's number one anti-phishing company, KnowBe4, Inc., this guide shows you how to create an enduring, integrated cybersecurity culture. - Learn what social engineering and phishing are, why they are so dangerous to your cybersecurity, and how to defend against them - Educate yourself and other users on how to identify and avoid phishing scams, to stop attacks before they begin - Discover the latest tools and strategies for locking down data when phishing has taken place, and stop breaches from spreading - Develop technology and security policies that protect your organization against the most common types of social engineering and phishing.
Online resource; title from title details screen (O'Reilly, viewed April 1, 2024)
Keywords: Phishing -- Prevention; Computer security; Electronic mail messages -- Security measures; Sécurité informatique; Courrier électronique; Sécurité; Mesures; Audiobooks; Livres audio